Risk Factor for Surgical Site Infection Post Sectio Caesarea - Dedeh Supriyatin; Margareta Melani; Siti Jubaedah; Ari Indra Susanti; Hadi Susiarno (Eduvest - Journal of Universal Studies, 2025)
Surgical site infections are infections that occur within 30 days of a surgical procedure, including infections in the post-sectio caesarea area that are common and can cause significant morbidity. This study aims to comprehensively identify and analyze the risk factors associated with post-sectio caesarea infection. The method used was a literature review with a PEO framework (Population: post-sectio caesarean section; Exposure: associated risk factors; Result: incidence of infection). Article searches were carried out systematically in official databases such as Google Scholar, Pubmed, Science Direct, and Scopus with the keywords "risk factors" AND "surgical site infections" AND "sectio caesarea", published 2018-2023. The results of the study found eight articles that showed risk factors for post-cesarean section infection, including: the number of vaginal examinations ≥ 5 times, rupture of the amniotic sac ≥ 12 hours, chorioamnionitis, long duration of labor (≥12 hours and ≥ 24 hours), estimated intraoperative blood loss of 500 to ≥ 1000 cc, intraoperative blood transfusion, emergency sectio caesarean section, operative duration of more than 1 hour,  previous history of cesarean section, obesity, diabetes mellitus, hypertension, and anemia. Understanding and managing infection risk factors effectively is expected to reduce the infection rate in the surgical area, and infection prevention can be done by implementing treatment packages.